Acute myeloid leukaemia in a patient with AIDS – case report - Kisiel, Elżbieta; Centkowski, Piotr; Warzocha, Krzysztof; Podlasin, Regina B. (Contemporary Oncology/Współczesna Onkologia, 2009)
HIV-infected subjects are at increased risk of developing several cancers. Three of them – Kaposi’s sarcoma, non-Hodgkin’s lymphoma and invasive cervical cancer – are accepted as AIDS-defining malignancies. Acute myeloproliferative diseases are rare in HIV-infected individuals. HIV-seropositive patients with acute myeloid leukaemia (AML) are presented in the literature as isolated case reports. We describe a case of acute myeloid leukaemia (FAB-M5a) with Kaposi’s sarcoma occurring in a HIV/EBV coinfected woman, sequentially treated with highly active antiretroviral therapy (ARV). She received treatment with a standard AML induction regimen consisting of infusion of cytarabine 200 mg/m 2 daily for 5 days, etoposide 100 mg daily for 5 days and idarubicin 10 mg/m 2 daily for 3 days, followed by double consolidation chemotherapy (I – cytarabine + mitoxantrone, II HD cytarabine). Complete remission (CR) lasting six months was achieved. HIV viral load increase was not observed. CD4+ cell count has remained above 200/µl. ARV has resulted in a significant decline of mortality and opportunistic infections, improving overall survival among HIV-infected patients. Conventional chemotherapy regimens often followed by haematopoietic stem cell transplantation have become commonly used. As acute myeloid leukaemia is rare in HIV-infected individuals, recommendations on treatment have not been defined and each case is treated individually.